The microstructure of avian eggshells, adaptive significance and practical implications in aviculture - Board, R G (Wildfowl, 1981)
Eggs laid in ’wet places’ need to be adapted so that the pore canals in the calcareous shell are not flooded with water or occluded with mud, nest debris, preening oils or salts. The shell of the Greater Flamingo Phoenicopterus ruber roseus was taken as an example. Its surface layer of spheres rich in calcium, phosphorus and sulphur is probably the adaptation that fits the egg to the nest environment. Field studies could establish the extent of the contribution of the outer layer of spheres to the well-being of the embryo.